Peripheral nerves electrostimulators. Technical Specifications - Mateusz Domeracki; Agnieszka Braun; Marcin Kożuchowski; Monika Prylińska; Natalia Skierkowska; Jakub Husejko; Beniamin Szmelcer; Agata Trzebiatowska; Michał Wilczyński (Journal of Education, Health and Sport, 2018)
Admission The first successful attempt to use stimulants neuro modulation properties date back to the first half of the twentieth century. Due to the high technological limitations, the use of peripheral nerve electrostimulators the early eighties